Consider a sequence of numbers T 1 , T 2 , T 3 , … , T n ( n ∈ Z + ) that satisfies the following: T 1 = 5 , d 1 = 3 T 2 = T 1 + d 1 T 3 = T 2 + d 2 ⋮ T n = T n − 1 + d n − 1 d k = d k − 1 + 1 , k = 2 , 3 , 4 , … , n − 1
Find T 1 1 5 3 .
Sequence Within A Sequence 2>>
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did the same (+1) Nice solution!
We claim that T n = T 1 + ( n − 1 ) d 1 + 2 ( n − 1 ) ( n − 2 ) = 5 + 2 ( n − 1 ) ( n + 4 ) and then prove it by induction.
T n + 1 = T n + d n Note that d n = d 1 + n − 1 = n + 2 = 5 + 2 ( n − 1 ) ( n + 4 ) + n + 2 = 5 + 2 n 2 + 3 n − 4 + 2 n + 4 = 5 + 2 n 2 + 5 n = 5 + 2 n ( n + 5 ) = 5 + 2 ( n + 1 − 1 ) ( n + 1 + 4 )
The claim is also true for n + 1 and therefore it is true for all n .
Therefore, T 1 1 5 3 = 5 + 2 ( 1 1 5 3 − 1 ) ( 1 1 5 3 + 4 ) = 5 + 5 7 6 × 1 1 5 7 = 6 6 6 4 3 7
The series 5, 8, 12, 17, 23, . . . expressed as 2 n 2 + 3 n + 6 , gives 666437 at n = 1153.
Problem Loading...
Note Loading...
Set Loading...
We have T 2 = T 1 + d 1 T 3 = T 2 + d 2 ⋮ T n = T n − 1 + d n − 1 Add all these equations together, cancelling out all the like terms we get T n = T 1 + d 1 + d 2 + d 3 + … + d n − 1 From the question, we know that d 1 , d 2 , … , d n − 1 is an A.P. (Arithmetic Progression).
Suppose d k − d k − 1 = D , k = 2 , 3 , … , n − 1 , using the sum of A.P. formula, we now have T n = T 1 + 2 n − 1 [ 2 d 1 + ( n − 2 ) D ]
Now, substitute n = 1 1 5 3 , T 1 = 5 , d 1 = 3 , D = 1 , we could get T 1 1 5 3 = 6 6 6 4 3 7 .